2017
DOI: 10.1002/jmor.20759
|View full text |Cite
|
Sign up to set email alerts
|

The anterior process of the malleus in extant Lagomorpha (Mammalia)

Abstract: The anterior anchoring of the malleus of 30 extant species of Lagomorpha (rabbits, hares, pikas) has been studied on the basis of histological serial sections and µCT-scans. It is shown that former studies of Oryctolagus, Lepus, and Ochotona are incomplete, because the rostral part of the processus anterior of the malleus is always lacking due to damage of this extremely delicate structure. Our study shows that in perinatal stages of Leporidae the praearticulare develops a prominent processus internus that fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…Thanks to its important integrative function, present‐day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al., 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al., 2013), humans, (Arechvo et al., 2013; Isaacson, 2014; Luers & Hüttenbrink, 2016; Sawada, Nara, Fukui, Dodo, & Hirata, 2014; Stieger, Djeric, Kompis, Remonda, & Häusler, 2006; Whyte et al., 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010; Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari‐Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006; Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015; Botti, Secci, Ragionieri, Dessole, & Acone, 2006; Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al., 2019; Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013; Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008; Charuta et al., 2011; Hoffstetter et al., 2011; Maier, Tröscher, & Ruf, 2018; Maravilla et al., 2011; Martonos et al., 2019; Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012; Wang & Gan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its important integrative function, present‐day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al., 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al., 2013), humans, (Arechvo et al., 2013; Isaacson, 2014; Luers & Hüttenbrink, 2016; Sawada, Nara, Fukui, Dodo, & Hirata, 2014; Stieger, Djeric, Kompis, Remonda, & Häusler, 2006; Whyte et al., 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010; Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari‐Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006; Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015; Botti, Secci, Ragionieri, Dessole, & Acone, 2006; Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al., 2019; Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013; Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008; Charuta et al., 2011; Hoffstetter et al., 2011; Maier, Tröscher, & Ruf, 2018; Maravilla et al., 2011; Martonos et al., 2019; Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012; Wang & Gan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Data related to the detailed anatomy of the auditory ossicles are relatively limited. A few elements were reported in case of birds (Mills, ), different rodents (Kerber & Sánchez‐Villagra, ; Kurtul et al, ; Lee, Park, Kang, & Choung, ; Li, Gao, Ding, & Salvi, ; Maier, Tröscher, & Ruf, ; Martins et al, ; Mohammadpour, , ; Şanlı, Sedat, & Oztürk, ), humans (García‐Real, Kass, Sturges, & Wisner, ; Isaacson, ), swine (Gurr, Kevenhörster, Stark, Pearson, & Dazert, ; Hoffstetter et al, ; Pracy, White, Mustafa, Smith, & Perry, ), miniature pigs (HaiJin et al, ), sheep (Ayres Seibel, Lavinsky, & Preto De Oliveira, ; Simaei, Soltanalinejad, Najafi, & Shalizar Jalali, ), chinchilla (Vrettakos, Dear, & Saunders, ; Wang & Gan, ), cat (Beck, Kilchling, & Meyer‐Lindenberg, ; Seifert et al, ), dog (Berghes, Parvu, Cucoanes, & Cuca, ) and wolf (Gürbüz et al, ), badger (Rozen‐Rechels, Peigné, Germain, & Ladevèze, ), horse (Blanke, Aupperle, Seeger, Kubick, & Schusser, ), donkey (Awal et al, ), common degu (32) or other subterranean cavimorphes (Argyle & Mason, ).…”
Section: Introductionmentioning
confidence: 99%
“…Terminology of the described structures follows Ekdale (2013Ekdale ( , 2016, Ruf (2014), Maier and Ruf (2014), and Maier et al (2018). The results concerning Palaeolagus haydeni are discussed in comparison to extant Lagomorpha based on data from literature (e.g., Ruf, 2014;Maier et al, 2018) and against the background of combined phylogeny from Matthee et al (2004), andMeng (2013). For grundplan reconstruction that allows defining all characters (apomorphic and plesiomorphic) of the last common ancestor of a respective taxon we follow the definition by Hennig (1984).…”
Section: Methodsmentioning
confidence: 99%
“…For grundplan reconstruction that allows defining all characters (apomorphic and plesiomorphic) of the last common ancestor of a respective taxon we follow the definition by Hennig (1984). The same scans of adult extant Lagomorpha included in the study on the auditory ossicles in Maier et al (2018) are used to discuss characters of the middle ear and the bony labyrinth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation